PENERAPAN HUKUM WARIS PERDATA DI INDONESIA - Aliya Sandra Dewi; Dian Fitriana; Elvira (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
All forms of inheritance, whether in the form of cash, land for rice fields owned by a person are called inheritance. Given to heirs openly or known to the wrong family, there is usually a will when receiving an inheritance with a message from the person giving the inheritance. Not all heirs have full rights to the inheritance, but there is a responsibility to maintain and develop the inheritance obtained according to the testator's wishes. Inheritance is a legacy of assets to heirs. There are three (3) types of application of inheritance law in Indonesia, namely Civil Inheritance Law, Islamic Inheritance Law, and Customary Inheritance Law. In this article the author focuses on the application of civil inheritance law in Indonesia. The method used is normative juridical research, namely a doctrinal method to study the application of rules or norms in positive law. With several approaches, the first is the Legislative Approach. Second, historical approach, third, comparative approach. The results of this discussion provide knowledge to the public that civil inheritance law recognizes 3 (three) principles, namely first, the individual principle (personal principle) where the heir is an individual, secondly the bilateral principle, namely that a person not only inherits from the father but also vice versa. mother, as well as brothers inheriting from their brothers and sisters, the third principle is the principle of degree, meaning that the heir whose rank is close to the heir covers the heir who is further away in rank, so to simplify the calculations, classifications are made heir.